Hungarian Monitoring, 22 July 1988 . [Magyar rádiófigyelő], 1988. július 22 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Iraq-Iran war - Czechoslovak missile disarmament - Survey of Karabakh situation Domestic Affairs: - Károly Grósz in San Francisco - Political Committee member István Szabó in Israel - Private sales of council apartments begin in Tolna and Baranya Counties - Gypsies and the skinheads in Borsod County - Water pollution from Romania, fish dying in Szamos Külpolitika - Irak-iráni háború - Csehszlovákiai rakétaleszerelések - Karabahi helyzekép Belpolitika: - Grósz Károly San Franciscoban - Szabó István PB tag Izraelben - Tolnában és Baranyában megkezdték a tanácsi lakások magánkézre adását - A borsodi cigányság és a bőrfejűek - Romániából érkező vízsszennyeződés, halpusztulás a Szamoson